Studying the Effect of Weather Conditions on some Properties of LDPE and Natural Wool Composite Material (Journal of Hama University, 2021)
In this research, natural wool was used as a natural additive to polyethylene in order to study the effect of its addition on some properties of the resulting composite material. Previous research was used through the processes of treating wool before adding, and it was concluded that at the weight percentage of 10% wool the higher rate of water absorption and the higher combustion time had been achieved, but compressive strength increases with the increase in the percentage of the additive. Then the effect of weather factors on the resulting material was studied, where it was placed in the out door atmosphere for a period of 4 months ; the tests were repeated and the difference was observed before and after exposure to weather factors